Application of Individual Quick Freezing (IQF) Technology for Freezing The Raw Materials of Sambal at UD Dede Satoe - Dego Yusa Ali; Teti Estiasih; Rini Yulianingsih; Riska Puspita; Lutfia Adila Putri; Brilliant Praditya (EQUATOR SINAR AKADEMIA, 2023)
The price of chili raw materials in Indonesia is influenced by several factors. These factors include erratic harvest seasons, the nature of perishable raw materials, poor post-harvest handling, and also supply and demand at the market. This is the cause of frequent fluctuations in the price of chili raw materials. Fluctuations in the price of chili raw materials are a problem in the chili production process at UD Dede Satoe. Thus, an inventory system is needed to store and freeze ingredients during rising material prices. The inventory system is an IQF refrigerator with dry ice freezing media. Dry ice is usually added to the cooling media because the ability to absorb the heat of a material by dry ice is greater than ordinary ice media. The use of dry ice in the freezing process aims to reduce the temperature of the material more quickly due to the large heat absorption ability caused by the low sublimation temperature point of dry ice, which is around -78.5oC. Thus, the material frozen with IQF refrigerators can extend the shelf life because it restrains microbial growth, maintains its nutritional and sensory quality.